APPLICATION OF VERTICAL ELECTRICAL SOUNDING (VES) IN GROUNDWATER AQUIFER ESTIMATION IN THE "SPR" AREA, WONOGIRI DISTRICT, WONOGIRI REGENCY, CENTRAL JAVA - Sepriyenra, Revaldo; Yatini, Y; Dewi, Ira Kusuma (Indonesian Physical Review, 2024)
â€œSPRâ€ area in Wonokarto Village, Wonogiri Regency, Central Java Province, is one area with serious groundwater problems. Regional conditions and significant population growth cause the need for clean water to increase. Efforts to obtain groundwater reserves continue to be made to overcome this problem. Identification of aquifers is carried out using resistivity methods. The research aims to determine the presence and types of an aquifer based on resistivity methods. Using the Schlumberger configuration, data was acquired at ten Vertical Electrical Sounding (VES) points. Results of the research show that in this region, tufa rocks form an aquifer layer in the Quarter Volcan Lava (Qvl) formation, with resistivity ranging from 14.9 to 29.8 Î©m. The â€œSPRâ€ area has three aquifer types, i.e., surface, shallow, and deep, with (1.5â€“5) meters, (10.5â€“25) meters, and (30â€“129) meters in depth, respectively.